Enforcement of State Administrative Law Against Abuse of Authority by Officials In the Acts of Corruption - Fitria Dewi Navisa (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2025)
This study employs a normative juridical method with qualitative analysis by examining legislation, court decisions, legal doctrine, and administrative enforcement practices related to abuse of authority. Case-based analysis is also applied to assess the implementation of the Administrative Court’s (PTUN) role in reviewing and determining acts of abuse of power prior to criminal proceedings. The findings reveal that abuse of authority in corruption cases often arises from weak internal oversight, poor ethical standards, and the ambiguous interpretation of administrative powers. The Administrative Court functions as a preventive and corrective mechanism by testing and annulling administrative decisions that exceed legal limits. However, the effectiveness of its role remains constrained by limited coordination between administrative and criminal justice systems. This study contributes by emphasizing the need to strengthen judicial oversight, ethical governance, and regulatory synergy to support a corruption-free administration.